The body (σῶμα) as tomb (σῆμα) of the soul in Philo of Alexandria. Use and resignification of a metaphor (Circe de clásicos y modernos, 2018)
The idea that the body (σῶμα) is a tomb (σῆμα) where the soul remains confined as a punishment for an ancient fault is transmitted by Plato, who attributes it to the orphics. Philo of Alexandria made use of this metaphor of orphic origin in various passages of his work. Our interest is to analyze the sense that Philo assigns to it and the way in which he reelaborates the meaning that was ascribed to it in orphic tradition and in the platonic interpretation. We will try to demonstrate that Philo uses the metaphor in two different ways that show the strong ambivalence existing in his thought with respect to the value of the human body.
Keywords: Philo; body; tomb; soul